Novel Biomarkers, ST‐Elevation Resolution, and Clinical Outcomes Following Primary Percutaneous Coronary Intervention. Issue 13 (7th July 2020) - Shavadia, Jay S.; Granger, Christopher B.; Alemayehu, Wendimagegn; Westerhout, Cynthia M.; Povsic, Thomas J.; Van Diepen, Sean; Defilippi, Christopher; Armstrong, Paul W.
Abstract : Background: Despite restoration of epicardial flow following primary percutaneous coronary intervention (PPCI), microvascular reperfusion as reflected by ST‐elevation resolution (ST‐ER) resolution remains variable and its pathophysiology remains unclear. Methods and Results: Using principal component analyses, we explored associations between 91 serum biomarkers drawn before PPCI clustered into 14 pathobiologic processes (including NT‐proBNP [N‐terminal pro‐B‐type natriuretic peptide] as an independent cluster), and (1) ST‐ER resolution ≥50% versus <50%; and (2) 90‐day composite of death, shock, and heart failure. Network analyses were performed to understand interbiomarker relationships between the ST‐ER groups. Among the 1160 patients studied, 861 (74%) had ST‐ER ≥50% at a median 40 (interquartile range, 23–70) minutes following PPCI, yet both groups had comparable post‐PPCI TIMI (Thrombolysis in Myocardial Infarction) grade 3 flow (86.6% versus 82.9%; P =0.25). ST‐ER ≥50% was associated with significantly lower pre‐PPCI concentrations of platelet activation cluster (particularly P‐selectin, von Willebrand factor, and platelet‐derived growth factor A) and NT‐proBNP, including after risk adjustment. Across both ST‐ER groups, strong interbiomarker relationships were noted between pathways indicative of myocardial stretch, platelet activation, and inflammation, whereas with ST‐ER <50% correlations between iron homeostasis and inflammation were observed. Of all 14 biomarker clusters, only NT‐proBNP was significantly associated with the 90‐day clinical composite. Conclusions: Suboptimal ST‐ER is common despite achieving post‐PPCI TIMI grade 3 flow. The cluster of platelet activation proteins and NT‐proBNP were strongly correlated with suboptimal ST‐ER and NT‐proBNP was independently associated with 90‐day outcomes. This analysis provides insights into the pathophysiology of microvascular reperfusion in ST‐segment–elevation myocardial infarction and suggests novel pre‐PPCI risk targets potentially amenable to enhancing tissue‐level reperfusion following PPCI.